Pijat Bayi terhadap Durasi Menyusu pada Bayi - Anita Ningsih Simangunsong; Rifa Yanti; Fajar Sari Tanberika; Nurhidaya Fitria (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of infant massage on breastfeeding duration in infants in Danau Rambai Village, within the Batang Gansal Community Health Center (Puskesmas), Indragiri Hulu Regency. The method used was a quantitative approach with a pre-experimental, one-group pretest-posttest design without a control group. The results of the study, using the Wilcoxon signed-rank test, yielded a p-value of 0.000 < 0.05. In conclusion, there is an effect of infant massage intervention on breastfeeding duration in infants in Danau Rambai Village, within the Batang Gansal Community Health Center, Indragiri Hulu Regency, in 2025.   Keywords: Infants, Breastfeeding Duration, Infant Massage